RELIGION, RELIGIOUS LEADERS AND STATEIN THE NORTH CAUCASUS DURING THE GREAT PATRIOTIC WAR - Halidova, O B (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with an aspect of historical problem of interaction of religion, religious organizations and the Soviet state during the Great Patriotic War. In the context of national policy in the religious sphere, the author of the article analyzes the techniques and methods ofwork of government agencies and their implementation in real life of the North Caucasian republics.
Keywords: Great Patriotic War; USSR; North Caucasus; state; religious organizations.